Oral morphine induces spinal 5‐hydroxytryptamine (5‐HT) release using an opioid receptor‐independent mechanism - Shingo Nakamura; Shuji Komatsu; Toshihiko Yamada; Hiromi Kitahara; Tatsuo Yamamoto (Wiley, 2023)
Abstract Morphine induces spinal 5‐hydroxytryptamine (5‐HT) release, but the role and mechanism of the spinal 5‐HT release induced by morphine are not well understood. The purpose of this study was to define the role and mechanism of spinal 5‐HT release induced by oral morphine. We also examined whether persistent pain affected the spinal 5‐HT release induced by oral morphine. Spinal 5‐HT release was measured using microdialysis of lumbar cerebrospinal fluid (CSF). Two opioids, morphine and oxycodone, were orally administered and 5‐HT release was measured in awake rats. Naloxone and β‐funaltrexamine (β‐FNA) were used to determine whether the effect of morphine on 5‐HT release was mediated by opioid receptor activation. To study persistent pain, a formalin test was used. At 45 min after oral morphine administration, the formalin test was started and spinal 5‐HT release was measured. Oral morphine, but not oral oxycodone, increased 5‐HT release at the spinal cord to approximately 4000% of the baseline value. This effect of morphine was not antagonized by either naloxone or β‐FNA at a dose that antagonized the antinociceptive effect of morphine. Formalin‐induced persistent pain itself had no effect on spinal 5‐HT release but enhanced the oral morphine‐induced spinal 5‐HT release. Oral morphine‐induced spinal 5‐HT release was not mediated by opioid receptor activation. Spinal 5‐HT induced by oral morphine did not play a major role in the antinociceptive effect of morphine in the hot plate test. Persistent pain increased oral morphine‐induced spinal 5‐HT release.